Pre‐diabetes and serum sex steroid hormones among US men. (28th October 2016) - Arthur, R.; Rohrmann, S.; Møller, H.; Selvin, E.; Dobs, A. S.; Kanarek, N.; Nelson, W.; Platz, E. A.; Van Hemelrijck, M.
Summary: Several studies demonstrate a link between diabetes and sex steroid hormones, but the link with pre‐diabetes remains elusive. In this study, we hypothesize that pre‐diabetes, which is characterised by having impaired fasting glucose and/or impaired glucose tolerance and/or impaired HbA1C, may influence circulating sex steroid hormone concentrations in men. Thus, we investigated whether serum sex steroid hormone concentrations differ between men with and without pre‐diabetes. We analyzed data for 1139 men who were aged 20+ years when they participated in the Third National Health and Nutrition Examination Survey. We calculated adjusted geometric mean serum concentrations of total and estimated free testosterone, androstanediol glucuronide, total and estimated free estradiol, and sex hormone‐binding globulin (SHBG) in men with and without pre‐diabetes. Logistic regression was used to calculate adjusted odds ratios (OR) of lower concentrations of androgens and SHBG, and higher concentrations of estradiol by prediabetes status. Adjusting for age and race/ethnicity, total testosterone concentration was lower among men with (geometric mean: 4.68 ng/mL) than without (5.36 ng/mL, p  = 0.01) pre‐diabetes. SHBG concentration was also lower in men with (31.67 nmol/L) than without (36.16 nmol/L; p  = 0.01) pre‐diabetes. Concentrations of the other hormones did not differ between men with and without pre‐diabetes. After adjusting for demographic and lifestyle factors, pre‐diabetic men had a higher odds of lower testosterone (OR: 2.58; 95% CI: 1.54–4.29), higher free estradiol level (OR: 1.59; 95% CI: 1.14–2.22), and lower SHBG level (OR: 2.27; 95% CI: 1.32–3.92) compared to men without pre‐diabetes. These associations were attenuated after adjusting for adiposity (testosterone OR: 1.76; 95% CI 0.95–3.27, free estradiol OR: 1.29, 95% CI: 0.88–1.88, SHBG OR: 1.71; 95% CI 0.88–3.30). Our findings suggest that men with pre‐diabetes have lower circulating total testosterone and SHBG and higher free estradiol levels.